2022
DOI: 10.1002/lsm.23542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water cooling on laser‐induced thermal damage in rat hepatectomy

Abstract: High-powered lasers are commonly used for tissue resection in surgeries, including liver resection, medically known as hepatectomy; however, such lasers inevitably induce thermal damage that causes postoperative complications. This study aims to explore the effects of water cooling and different laser output modes on laser-induced thermal damage during hepatectomy. Methods: To avoid the influence of superposition, a 980-nm diode laser was used for a single-point hepatectomy. Eighteen Sprague-Dawley rats were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Concerning the diode laser, only two published scientific studies have evaluated the effects of water/air spray cooling systems on pork liver, using a micropulsed mode of 980-nm diode laser. [ 11 30 ] In the present study, the coolant action of saline was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the diode laser, only two published scientific studies have evaluated the effects of water/air spray cooling systems on pork liver, using a micropulsed mode of 980-nm diode laser. [ 11 30 ] In the present study, the coolant action of saline was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, conducted by Shan et al . [ 30 ] using water cooling system with 980 nm for hepatectomy in rats, concluded that water cooling can reduce the carbonized area and total laser-induced thermal damage area. These discoveries are especially crucial for practical use since they immediately improve wound healing by reducing permanent collateral tissue damage.…”
Section: Discussionmentioning
confidence: 99%